Analysis of Visitors’ Satisfaction on the Quality of Omah Salak Agro Tourism Services - Mar'atul Karimah; Agus Setiadi; Mukson Mukson (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
The development of the agricultural sector into agro tourism is carried out to realize the desires of people who wish for educational and environment-friendly tourism activities. Omah Salak Agro Tourism provides a variety of reservation packages, culinary packages, and souvenirs of processed zalacca products. Consumer satisfaction to the services is an important factor to be considered. This study aimed to analyze visitor satisfaction with the quality of services including physical evidence, reliability, responsiveness, assurance, and care given by Omah Salak Agro Tourism. The study used a case study method with a sample size of 100 respondents. The sampling method used was purposive sampling technique. The measurement scale used was the Likert scale. Data analysis methods used were the customer satisfaction index (CSI), gap analysis, and importance performance analysis (IPA). The results of the analysis showed a CSI value of 77.44%, meaning that overall visitors were satisfied with the service performance at the Omah Salak Agro Tourism. The results of the gap analysis showed the performance <importance with a value of 3.87 <4.33, the average gab was -0.46, meaning that the Omah Salak Agro Tourism service has not met the wishes of the visitors. The results of the IPA analysis showed that the top priority attributes for the improvement of Omah Salak Agro Tourism are the availability of worship facilities, bathroom facilities, adequate parking facilities, timely events, friendly and courteous guides and company staff to make visitors feel safe